Hypoxia-Enhanced N2O Production Under Ocean Acidification in the Bohai Sea - Gu, Ting; Jia, Dai; Ma, Xing; Peng, Liying; Zhang, Guicheng; Wei, Yuqiu; Lou, Tingting; Sun, Jun (Frontiers in Marine Science, 2021)
Nitrous oxide (N2O) is a powerful greenhouse gas that degrades ozone. Hypoxia and ocean acidification are becoming more intense as a result of climate change. The former stimulates N2O emissions, whereas the effects of the latter on N2O production vary by the ocean. Hypoxia and ocean acidification may play a critical role in the evolution of future oceanic N2O production. However, the interactive effects of hypoxia and ocean acidification on N2O production remain unclear. We conducted a research cruise in the Bohai Sea of China to assess the occurrence of ocean acidification in the seasonal oxygen minimum zone of the sea and further conducted laboratory incubation experiments to determine the effects of ocean acidification and hypoxia on N2O production. When pH decreased by 0.25, N2O production decreased by 50.77 and 72.38%, respectively. In contrast, hypoxia had a positive impact; when dissolved oxygen (DO) decreased to 3.7 and 2.4 mg L−1, N2O production increased by 49.72 and 278.68%, respectively. The incubation experiments demonstrated that the coupling of ocean acidification and hypoxia significantly increased N2O production, but, individually, there was an antagonistic relationship between the two. Structural equation modeling showed that the total effects of hypoxia treatment on N2O production changes weakened the effects of ocean acidification, with overall positive effects. Generally speaking, our results suggest that N2O production from the coastal waters of the Bohai Sea may increase under future climate change scenarios due to increasingly serious ocean acidification and hypoxia working in combination.